Neutrophil extracellular trapping and angiogenesis biomarkers after intravenous or inhalation anaesthesia with or without intravenous lidocaine for breast cancer surgery: a prospective, randomised trial. (November 2020) - Galoș, Elena V.; Tat, Tiberiu-Florin; Popa, Răzvan; Efrimescu, Catalin-Iulian; Finnerty, Dylan; Buggy, Donal J.; Ionescu, Daniela C.; Mihu, Carmen M.
Abstract: Background: Experimental and, retrospective, clinical data indicate that anaesthetic technique might influence the risk of metastasis after cancer surgery. Neutrophil extracellular trapping (NETosis) is an immunological mechanism strongly linked with increased metastatic risk. Similarly, vascular endothelial growth factor A is linked to angiogenesis implicated in recurrence. Therefore, we investigated the effect of four anaesthetic techniques on NETosis and angiogenic factors expression in women undergoing breast cancer resection. Methods: Women ( n =120) undergoing primary breast tumour resection were randomly assigned to receive one of four anaesthetics: sevoflurane (S), sevoflurane plus i.v. lidocaine (SL), propofol (P), and propofol plus i.v. lidocaine (PL). Venous blood was collected before induction and 20–28 h after operation. Neutrophil myeloperoxidase and citrullinated histone H3, biomarkers of NETosis, and biomarkers of angiogenesis were measured by enzyme-linked immunosorbent assay. Results: Patient characteristic data and perioperative management did not differ between study groups. The anaesthetic technique including lidocaine decreased expression of citrullinated histone H3 compared with no lidocaine (109 [23] vs 125 [22] ng ml −1, P =0.01 for SL and S and 98 [14] vs 130 [32] mg ml −1, P =0.007, for PL and P, respectively). Similarly, myeloperoxidase was decreased by lidocaine (8.5 [3.4] vs 10.8 [1.8] ng ml −1, P =0.03 for SL and S and 8.6 [3.1] vs 11.6 [2.5] ng ml −1, P =0.01 for PL and P, respectively). Lidocaine also decreased expression of matrix metalloproteinase 3 (MMP3) but not MMP9, whichever anaesthetic was used. Vascular endothelial growth factor A concentrations were not significantly influenced by the anaesthetic technique. Conclusions: I.V. perioperative lidocaine decreased postoperative expression of NETosis and MMP3, regardless of general anaesthetic technique. This supports the hypothesis that i.v. lidocaine during cancer surgery of curative intent might reduce recurrence. Clinical trial registration: NCT02839668 .